Natural and anthropogenic forcing of multi-decadal to centennial scale variability of sea surface temperature in the South China Sea - Goodkin, Nathalie Fairbank (2022)
Four hundred years of reconstructed sea surface temperatures (SSTs) from a coral located off the coast of Vietnam show significant multi-decadal to centennial-scale variability in wet and dry seasons. Wet and dry season SST co-vary significantly at multi-decadal timescales, and the Interdecadal Pacific Oscillation (IPO) explains the majority of variability in both seasons. A newly reconstructed wet season IPO index was compared to other IPO reconstructions, showing significant long-term agreement with varying amplitude of negative IPO signals based on geographic location. Dry season SST also correlates to sea level pressure anomalies and the East Asian Winter Monsoon, although with an inverse relationship from established interannual behavior, as previously seen with an ocean circulation proxy from the same coral. Centennial-scale variability in wet and dry season SST shows 300 years of near simultaneous changes, with an abrupt decoupling of the records around 1900, after which the dry season continues a long-term cooling trend while the wet season remains almost constant. Climate model simulations indicate greenhouse gases as the largest contributor to the decoupling of the wet and dry season SSTs and demonstrate increased heat advection to the western South China Sea in the wet season, potentially disrupting the covariance in seasonal SST.